Editorial: Experiments and field observations: Two predominant aspects of a multi-faceted vegetation science - Chiarucci, Alessandro (2007)
Each year, the Chief Editors of the Journal of Vegetation Science choose one of the papers nominated by Coordinating Editors and Referees, for the Editors´ Award for their quality, novelty or clarity in approaching a topic in vegetation science. There is no financial or other reward, just glory for the authors! For this year, there were eight papers nominated.The paper selected for the Editors´ Award was that by Carlyle & Fraser (2006). This paper reports an experiment, performed under controlled greenhouse conditions, to test the Competitive Response (CR) strategy model in 19 species typical of wet meadows in Northeast Ohio, USA. Each species was placed into one of three strategies based on variation in the CR strategy of juvenile plants growing under a canopy: (1) persist; (2) escape; (3) forage. The three possible strategies were tested with well-planned experiments and then checked for correlations with classic plant traits such as seed size or plant biomass.